KONSEP MAQASHID AL-SYAR’I IMAM AL-SYATHIBI DALAM STUDI HERMENEUTIKA AL-QUR’AN - Rasy Rahmania Alfaatih; Meilia Geminda Br. Ginting; Desi Awaliya Br. Margolang; Genta Nofriadi (Sekolah Tinggi Ilmu Al-Qur'an Ar-Rahman, 2024)
As-Syathibi is one of the famous scholars and experts in the science of jurisprudence. He was born in Granata in 730 AH and died in 790 AH. He was known as a qualified scholar in various scientific disciplines such as Arabic, philosophy, kalam science, tafsir and hadith as well as fiqh and ushul fiqh. He has many works, one of which is Kitab al-Muqafaqat fi Ushul al-Shari'ah. It is this book that makes al-Shathibi known as the father of maqashid al-Shar'i. Imam al-Shathibi divided the discussion of maqashid al-Shar'i into 2, namely qasd al-Shar'i and qashd al-Mukallaf. In this article, the author will explain and explain the biography, works and concepts of maqashid al-Shar'i according to al-Shathibi. This research uses library research method with qualitative approach.